2018
DOI: 10.1115/1.4040774
|View full text |Cite
|
Sign up to set email alerts
|

Cyclogram-Based Joint Symmetry Assessment After Utilization of a Foot Drop Stimulator During Post-stroke Hemiplegic Gait

Abstract: In the absence of standardized symmetry assessments, quantifying symmetry based on the kinematic evolution of lower extremity joints can elucidate gait irregularities. The objective was to develop a novel cyclogram based symmetry (CBS) method to quantify lower extremity joints' symmetry and assess the effect of 6-month utilization of foot drop stimulator (FDS) on CBS of the lower limbs during hemiplegic gait post stroke. Twenty-four participants (13 stroke and 11 healthy controls (HC)) performed 10 walking tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Moreover, interpretation of the parameters they provide is not so straightforward as occurs with classic symmetry indexes. However, several studies carried out in the last decade on individuals affected by neurologic (neuropathies, stroke, Parkinson's disease [25][26][27]) and orthopedic conditions [28][29][30] demonstrated that such an approach is versatile and allows a more accurate and thorough analysis of gait symmetry, thus proving to be of great relevance in all conditions characterized by subtle, not easily detectable alteration of gait with the conventional discrete indices.…”
Section: Waveform-based Methods To Assess Interlimb Symmetry During Gaitmentioning
confidence: 99%
“…Moreover, interpretation of the parameters they provide is not so straightforward as occurs with classic symmetry indexes. However, several studies carried out in the last decade on individuals affected by neurologic (neuropathies, stroke, Parkinson's disease [25][26][27]) and orthopedic conditions [28][29][30] demonstrated that such an approach is versatile and allows a more accurate and thorough analysis of gait symmetry, thus proving to be of great relevance in all conditions characterized by subtle, not easily detectable alteration of gait with the conventional discrete indices.…”
Section: Waveform-based Methods To Assess Interlimb Symmetry During Gaitmentioning
confidence: 99%
“…Waveform-based methods exploit the whole kinematic data associated with a certain lower limb joint angle with time throughout the whole gait cycle and thus enrich the information content useful to quantify symmetry. This approach was successfully applied in the last decade to investigate inter-limb coordination in several pathologic populations affected by both neurologic (neuropathies, stroke, Parkinson's disease, and multiple sclerosis) [28][29][30][31][32] and orthopaedic conditions [33][34][35]. In most cases, the use of waveform-based methods resulted more effective in detecting subtle alterations of gait with respect to discrete symmetry indices.…”
Section: Introductionmentioning
confidence: 99%
“…13 Mechanisms of walking after ABI are often characterized by reduced speed, kinematic, temporospatial, and neuromuscular asymmetry, and postural instability. [14][15][16][17] Therefore, one of the major rehabilitation goals for individuals after ABI is to improve mobility and regain functional independence in the community. 18 Numerous interventions are being developed based on exercise, physical therapy, functional electrical stimulation, and robotic exoskeletons.…”
Section: Introductionmentioning
confidence: 99%
“…Hemiparesis, which persists even into the chronic phase of stroke, affects balance and reduces a person's ability to walk 13 . Mechanisms of walking after ABI are often characterized by reduced speed, kinematic, temporospatial, and neuromuscular asymmetry, and postural instability 14‐17 . Therefore, one of the major rehabilitation goals for individuals after ABI is to improve mobility and regain functional independence in the community 18 .…”
Section: Introductionmentioning
confidence: 99%